Effect of different microbubble generation methods on growth of Japanese mustard spinach. (2nd January 2017) - Ikeura, Hiromi; Takahashi, Hideaki; Kobayashi, Fumiyuki; Sato, Michio; Tamaki, Masahiko
ABSTRACT: To provide the necessary oxygen for plant growth, the effectiveness of different generating methods of microbubbles (MB), a gas-water circulation type or a pressurization type (pressurization treatment), was investigated by comparing the growth characteristics and morphological observation of Brassica campestris L. var. Komatsuna Matsum. The plant growth in the pressurization treatment were significantly less than those in the circulation treatment at 3 weeks after planting. In plants grown in the pressurization treatment, epidermal cell abrasion and plasmolysis, indicators of cell death, were observed in root tip cells at 3 weeks after planting. The growth inhibition of plant in the pressurization treatment is suggested to be related to the oxidization of Fe in the nutrient solution under super-saturated dissolved oxygen conditions, the generation of hydroxyl radicals from MB, the oxidization of the root tip cell membrane, and osmotic stress to the roots.